2021
DOI: 10.2147/ijgm.s295627
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exposure Prophylaxis for COVID-19 in Pregnant Women

Abstract: Pregnant women are at higher risk for developing severe complications of COVID-19 including preterm delivery, respiratory failure, and death. Although vaccines to prevent COVID-19 are being developed, pregnant women are not included in the current COVID-19 vaccine trials and initially this population may not be eligible for COVID-19 vaccines due to lack of safety testing in pregnancy. As an alternate approach, we discuss the concept of pre-exposure prophylaxis (PrEP) using medications that are approved for use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…For (pre-exposure) prophylaxis in pregnancy, where vaccines may be contraindicated, the alternative of hydroxychloroquine has been advocated. 125 , 126 In addition to safety and relative efficacy, different risk–benefit judgments may be presented for prophylaxis (pre- and post-exposure), and for treatment, with pregnancy a high-risk status for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For (pre-exposure) prophylaxis in pregnancy, where vaccines may be contraindicated, the alternative of hydroxychloroquine has been advocated. 125 , 126 In addition to safety and relative efficacy, different risk–benefit judgments may be presented for prophylaxis (pre- and post-exposure), and for treatment, with pregnancy a high-risk status for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…preventing SARS-CoV-2 infection in pregnant women, thereby averting undesirable complications and risks for the mother and the fetus. 14 To the best of our knowledge, this report is the first case of urticarial vasculitis in a pregnant woman with COVID-19. An additional novelty of this case is the identification of mucin deposition in the upper dermis, which may be a new histological feature of vasculitis seen in COVID-19.…”
Section: Discussionmentioning
confidence: 72%
“…13 Considering the lack of studies on the safety of COVID-19 vaccination in pregnant women, the alternative option of using hydroxychloroquine as a prophylactic medication to prevent severe complications and gestational problems in this population has been discussed. 14 Many studies have confirmed the antiviral and anti-inflammatory features of hydroxychloroquine, which may be useful in F I G U R E 2 (A-C) Sections show skin tissue with normal epidermal thickness, mild basket weave orthokeratosis, mild spongiosis, and focal vacuolar interface reaction. There is mild perivascular infiltration of lymphocytes in the upper dermis accompanied by swelling of endothelial cells, narrowing of the vascular lumen, and mild extravasation of red blood cells.…”
Section: Discussionmentioning
confidence: 95%
“…The clinical and physiological characteristics of pregnant women make them vulnerable to coronavirus disease (COVID-19) and its complications [1]. It is believed that pregnant women have no greater risk of developing complications due to COVID-19; however, studies have shown an increased risk of morbidity, respiratory failure, mechanical ventilation, and death among these patients [2][3][4]. As an increase in maternal deaths has been reported, greater assistance for the maternal-fetal dyad during the COVID-19 pandemic is required [1].…”
Section: Highlights ключевые положенияmentioning
confidence: 99%
“…and Stricker R.B. [4] have suggested that hydroxychloroquine can even be used prophylactically in the pre-exposure of pregnant women to COVID-19 as this drug is safe during pregnancy and could prevent gestational complications and serious evolution in this high-risk population. The proposal would be to offer hydroxychloroquine 400 mg weekly to this population [4].…”
Section: Treatment Of the Initial Stage Of The Diseasementioning
confidence: 99%